'Treat me with respect': transgender persons' experiences of encounters with healthcare staff. Issue 2 (20th July 2020) - Carlström, Rebeccah; Ek, Susanna; Gabrielsson, Sebastian
Abstract : Background: Transgender persons face barriers to health care including discrimination and lack of awareness by professionals. This study aimed to describe transgender persons' experiences of encounters with healthcare staff. Methods: Participants were recruited through postings in social media and on websites targeting people identifying as transgender. Through an online form, 21 people identifying as transgender provided written self‐reports. These were analysed using a method for inductive qualitative content analysis. The study was conducted in Sweden in 2018. Results: The results describe transgender persons' experiences and perceptions of encounters with healthcare staff in one theme: treat me with respect, and three main categories: accept me for who I am; treat me according to my needs; and meet me with competence . Conclusions: Healthcare professionals can contribute in restoring and upholding transgender people's trust in health care by accepting their identity and focusing on their healthcare needs while also being informed about transgender people's needs and realities. A key point in this is recognising transgender person's vulnerability to violations of dignity in relation to health care.